The Influence of Financial Knowledge, Positive Emotions, and Store Atmosphere on College Students' Impulsive Buying - Nida Hanifah; Muhammad Sabandi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2026)
Impulse buying refers to spontaneous purchasing behavior that occurs without prior planning and is often influenced by emotional and environmental factors. This study aims to analyze the effects of financial knowledge, positive emotions, and store atmosphere on impulse buying behavior among university students. This research employed a descriptive quantitative approach and was grounded in Social Cognitive Theory, which posits that behavior results from the interaction between personal, behavioral, and environmental factors. The sample consisted of 268 students from the Economic Education study program who were selected using a proportionate random sampling technique and had completed at least one course related to finance. Data were collected through a closed-ended questionnaire and analyzed using multiple linear regression after passing tests of validity, reliability, and classical assumptions. The results indicate that financial knowledge, positive emotions, and store atmosphere have both partial and simultaneous effects on impulse buying behavior. These findings highlight the importance of financial knowledge and awareness of emotional and environmental influences in controlling impulse buying among university students. The findings further imply that strengthening students’ financial knowledge should be reinforced through the integration of financial literacy into the learning process, enabling students to manage consumption decisions more rationally.